PENINGKATAN KERJA SAMA EKONOMI DIGITAL AUSTRALIA DAN SINGAPURA DENGAN DISEPAKATINYA SINGAPORE AUSTRALIA DIGITAL ECONOMY AGREEMENT (SADEA) TAHUN 2020 - Habib Muhammad Zhorfan; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study tried to explore the reasons for the agreement of the Singapore - Australia Digital Economy Agreement (SADEA) to increase digital economy cooperation carried out by Australia and Singapore in 2020, from Australia’s point of view. The digital economy is an economic field that has very high potential and will continue to develop until the development of technology stops. SADEA is a bridge for Australia and Singapore to reduce barriers to digital trade for businesses and consumers through a series of new digital economy cooperation indicators. In addition to improving bilateral relations between the two countries, Australia also views that SADEA contributes to the economic interests of emerging digital technology companies in Australia, and can improve Australia's bargaining position in regional or multilateral digital economy forums such as the WTO. This research used Liberalism as a perspective, International Cooperation theory, and a nation-state level of analysis. As for the research method, the author used qualitative research methods accompanied by library research data collection techniques, which collect data from books, journals, articles, or websites. This research showed that Singapore is a potential partner for digital economy. In Southeast Asia, Singapore is the world's largest economic hub for region. Policy support from the government in responding to digital economic opportunities has resulted in an advanced digital environment output for the wider community, both in the community, business, and government sectors. Both Australia and Singapore previously developed a series of economic policies such as a free trade area and a comprehensive strategic partner. In addition, the two countries are also members of the countries that proposed the Joint Statement Initiative (JSI) on E-commerce at the WTO. Keywords: SADEA, Digital Economy, International Cooperation.